Carers and Professionals' Perspectives on Foster Care Outcomes: The Role of Contact - Delgado, Paulo (2018)
This study investigates the association between the contact of children or young people in care with their family, and the foster care placement evaluation (positive or negative) in Portugal. According to the perspectives of foster carers and service professionals’ perceptions regarding children and young people’s reactions, during and after the visits, are measured. Utilizing a quantitative approach, two fostering services teams and 140 foster carers completed questionnaires, which had 212 children in common. Results indicated that despite the importance of continued contact, especially for children and their parents, it was not determined to be essential to long-term placement. On one hand, there was the perception that a high percentage of children expressed positive reactions during and after the visit, while on the other hand, this didn’t in ﬂuence the perception of placement success. This study also showed signiﬁcant differences between foster carers’ and the professionals’ perceptions on several dimensions of foster care, especially the children’s reactions during visits. These differences need to be further analyzed in future research and the outcomes used to help improve contact management.